Kedisiplinan Mahasiswa Uin Saizu Purwokerto; Analisis Etos Kerja Max Weber: ANALISIS ETOS KERJA MAX WEBER - Fatih zidan nur, Fadli; Tiya Dwi Rara, Berliana; Nilna Nurila, Asabti; Muhammad, Inam (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2024)
The life of students studying while working is a common phenomenon, but it is unique when it is related to work ethic and discipline in study activities. The relationship between students and work is reflected in a person's behavior at work. Students who have superior human resource (HR) quality can be demonstrated by disciplined behavior, creativity, and a high work ethic in carrying out their duties and obligations during the learning process at college. If a student has a good concept of learning then the student will not delay carrying out his studies. This paper is the result of field research which discusses student discipline and its relationship with work ethic. The purpose of this research is to see the level of student ability in the field of discipline and student work ethic. This phenomenon is related to students' work ethic in forming personality traits in the process of behavior, especially in the context of students dividing their time at work and being active students in lectures. This work ethic is important to explore because it is the basis for students' existence values ​​at work.